Analysis of Translation Strategy of Mandarin Idioms (Chéngyǔ) in The Novel Little Mushroom《小蘑菇》by Yīshísì Zhōu - Dian Sari, Unga Waru; Putri, Alifia Maulidya; Khaerana, A. ST. Aldilah (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2025)
This study aims to describe the idiom translation strategies used by translators in translating the Mandarin Idiom 成语 chéngyǔ contained in the novel Little Mushroom《小蘑菇》Xiǎo Mógū by 一十四洲 Yīshísì Zhōu. This study uses a qualitative method with a descriptive approach. Data were collected using literature study techniques, and analyzed based on the theory of idiom translation strategies by Baker (2018). The results of the study showed that out of 164 Mandarin idioms 成语 chéngyǔ, the idiom translation strategy most used by translators was the paraphrase idiom translation strategy with a percentage of use reaching 62.25% and the least was the idiom translation strategy using the target language idiom that has a similar meaning and form with the number of data only 3 data (1.8%). The Mandarin idiom 成语 chéngyǔ has become an inseparable part of Chinese culture, because the Mandarin idiom 成语 chéngyǔ itself is a written cultural heritage, where the Mandarin idiom 成语 chéngyǔ has its own origins which come from famous stories in the past, mythology, and even the analects.